Health-Related Quality of Life Among Long-Term Survivors of Colorectal Cancer: A Population-Based Study - Caravati-Jouvenceaux, Agnès (AlphaMed Press, 2011)
BACKGROUND. The number of long-term colorectal cancer survivors is increasing. Cancer and its treatment can cause physical and psychological complications, but little is known about how it impacts quality of life (QOL) over the long term—5, 10, and 15 years after diagnosis. METHODS. Cancer survivors were randomly selected from three tumor registries in France, diagnosed in 1990 (±1 year), 1995 (±1 year), and 2000 (±1 year). Controls were randomly selected from electoral rolls, stratifying on gender, age group, and residence area. Participants completed two QOL questionnaires, a fatigue questionnaire, an anxiety questionnaire, and a life conditions questionnaire. An analysis of variance was used to compare QOL scores of cancer survivors by period of diagnosis (5, 10, and 15 years) with those of controls, adjusted for sociodemographic data and comorbidities. RESULTS. We included 344 colon cancer and 198 rectal cancer survivors and 1,181 controls. In a global analysis, survivors reported a statistically and clinically significant lower score in social functioning 5 years after diagnosis and higher scores in diarrhea symptoms 5 and 10 years after diagnosis. In subgroup analyses, rectal cancer affected QOL in the physical dimensions at 5 years and in the fatigue dimensions at 5 and 10 years. CONCLUSION. Survivors of colorectal cancer may experience the effects of cancer and its treatment up to 10 years after diagnosis, particularly for rectal cancer. Clinicians, psychologists, and social workers must pay special attention to rectal cancer survivors to improve overall management.